2012
DOI: 10.1002/term.1589
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun fibre diameter, not alignment, affects mesenchymal stem cell differentiation into the tendon/ligament lineage

Abstract: Efforts to develop engineered tendons and ligaments have focused on the use of a biomaterial scaffold and a stem cell source. However, the ideal scaffold microenvironment to promote stem cell differentiation and development of organized extracellular matrix is unknown. Through electrospinning, fibre scaffolds can be designed with tailorable architectures to mimic the intended tissue. In this study, the effects of fibre diameter and orientation were examined by electrospinning thin mats, consisting of small (< … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 53 publications
6
97
0
Order By: Relevance
“…54 In contrast, a recent study by Cardwell et al showed that human mesenchymal stem cells proliferate and differentiate better on microfibers than on nanofibers. 55 In our study, the correction efficiency on PCL-chitosan was comparably higher than those on PCL and PCL-lecithin during the recovery period (at Day 4), and it dropped significantly during the extended period. An explanation for this observation might be that a component released from the dissolved chitosan fiber interacts with cells to trigger a different pathway of physiology over the time.…”
supporting
confidence: 45%
“…54 In contrast, a recent study by Cardwell et al showed that human mesenchymal stem cells proliferate and differentiate better on microfibers than on nanofibers. 55 In our study, the correction efficiency on PCL-chitosan was comparably higher than those on PCL and PCL-lecithin during the recovery period (at Day 4), and it dropped significantly during the extended period. An explanation for this observation might be that a component released from the dissolved chitosan fiber interacts with cells to trigger a different pathway of physiology over the time.…”
supporting
confidence: 45%
“…Both these characteristics can be controlled and ordered when the new design is approached 40,44 . The tendon-engineered scaffolds should have fibre diameters varying between nano-scale and micro-scale 57,58 . It has been shown that controlling the scaffold fibre diameter is critical in the design of scaffolds for functional and guided connective tissue repair, and provides new insights into the role of matrix parameters in guiding soft tissue healing 57,58 .…”
mentioning
confidence: 99%
“…The tendon-engineered scaffolds should have fibre diameters varying between nano-scale and micro-scale 57,58 . It has been shown that controlling the scaffold fibre diameter is critical in the design of scaffolds for functional and guided connective tissue repair, and provides new insights into the role of matrix parameters in guiding soft tissue healing 57,58 . A tendon's normal architecture is composed of collagen fibrils with nanometric diameters and collagen fibres and fibre bundles with different micrometric diameters.Therefore, a suitable scaffold for tendon tissue engineering should consist of both micro and nanoscale moderately to highly aligned fibres to be effective in guiding both the nano and microstructure of the newly regenerated tissue after implantation 14,40,44 .…”
mentioning
confidence: 99%
“…Liu et al (2012) explain that arrangement of collagen scaffold has an important role in cellular arrangement in vitro. Cardwell et al (2012) also reported that large fibers are more efficient than arranged fibers in cell attitude in vitro. In present study both PRFM and PECM are considered as a 3D-architecture aligned in nature these matrices degraded gradually and its remnant act as micro scaffolds for newly tendon formation that result in healing tissue augmentation along the normal orientation of tendon fibers (Meimandi-Parizi et al, 2013).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 95%